Repair of bilateral abdominoscrotal hydrocele with testicular dysmorphism using laparoscopic extracorporeal ligation of the internal inguinal ring and orchiopexy - Yukihiro Tatekawa, MD (Elsevier, 2017)
On abdominoscrotal hydrocele (ASH), there are reports described about the excision of ASH by scrotal/inguinal approach or the laparoscopic-assisted surgery. A case of 8-month-old boy with bilateral ASH and testicular dysmorphism is reported herein. Repair of enlarged internal inguinal ring was done by laparoscopic extracorporeal ligation using an epidural needle and preperitoneal hydrodissection. Marsupialization of the hydrocele testis was done via the scrotal approach, and Nelaton catheters were inserted into the cavity of the hydrocele testis to inflate and deflate the cavity. This allowed clarification of the weak point of the peritoneum in the internal inguinal ring and confirmation of the opening of the process vaginalis. After orchiopexy, the laparoscopic findings showed the ligated peritoneum in the both sides became still more tighter on laparoscopy. It is postulated that simple closure of the internal inguinal ring without excision of the hydrocele might offer a laparoscopic cure for ASH.